2015
DOI: 10.5005/jp-journals-10024-1756
|View full text |Cite
|
Sign up to set email alerts
|

Surface Texture and Optical Properties of Self-Adhering Composite Materials after Toothbrush Abrasion

Abstract: This study evaluated the surface texture and optical properties of two self-adhering composites and a nanofilled composite before and after toothbrush abrasion. Vertise Flow (Kerr), Fusio Liquid (Pentron Clinical) and Filtek Z350 XT (3M ESPE) composites were divided into 3 groups (n = 6). Disks of 12 mm diameter and 2 mm thick were made. All materials were light-cured with a LED light source for 40 seconds. Analyses of surface roughness, gloss retention and color stability were performed 24 hours after light c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Çelik et al [18], and Malavasi et al [26]. However, at 12 months, statistical analysis showed that Fusio Liquid Dentin showed statistically higher prevalence of score 1 and lower prevalence of score 2 than Flow-It ® .…”
Section: Period Scorementioning
confidence: 99%
“…Çelik et al [18], and Malavasi et al [26]. However, at 12 months, statistical analysis showed that Fusio Liquid Dentin showed statistically higher prevalence of score 1 and lower prevalence of score 2 than Flow-It ® .…”
Section: Period Scorementioning
confidence: 99%
“…31 After toothbrushing abrasion, Vertise flow had a rougher surface compared to that resulting from the application of Fusio liquid dentin and a conventional restorative composite. 32 Results can be related to the type of organic matrix, since urethane-based composites have a better wear resistance than Bis-GMA-based composites, other factors being equal. 33 SACs also showed a much poorer performance in terms of gloss retention than a conventional control.…”
Section: Strategy 1: Self-adhesive Restorative Compositesmentioning
confidence: 99%
“…33 SACs also showed a much poorer performance in terms of gloss retention than a conventional control. 32 Self-adhesive composites are more hydrophilic than conventional composites due to the presence of acidic monomers and HEMA. In fact, Vertise Flow showed much higher hygroscopic expansion 34 and higher water sorption 35 when compared with conventional composites after 150 days in water.…”
Section: Strategy 1: Self-adhesive Restorative Compositesmentioning
confidence: 99%
“…Mainly used as liner or as repair material, they could also be applied as filling material in conservative preparations (2). The current novelty in adhesive dentistry is the development of self-adhesive flowable composites (SAFCs) to reduce the clinical time and to decrease the technique sensitivity (3).…”
Section: Introductionmentioning
confidence: 99%
“…The current novelty in adhesive dentistry is the development of self-adhesive flowable composites (SAFCs) to reduce the clinical time and to decrease the technique sensitivity (3). The SAFCs formulation is based on both conventional methacrylate system and acidic monomers bonding technology derived from self-etching adhesive systems (2). The acidic functional monomers are predominantly methacrylate acid-derivatives, such as 4-methacryloxyethyl anhydride trimellitate acid (4-META), or phosphonate monomers derivatives, such as 2-methacryloxyethyl phenyl phosphate (phenyl-P), methacryloyloxydecyl dihydrogen phosphate (10-MDP), and bis [2-(methacryloyloxy) ethyl] phosphate (2MP) (4).…”
Section: Introductionmentioning
confidence: 99%